SYSTEMATIC LITERATURE REVIEW: INVESTIGATIVE AUDITING IN FRAUD DISCLOSURE - muhammad syahrudin; irma Suryani; R. Wedi Rusmawan Kusumah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
In terms of global economic growth, Indonesia ranks 40th with the best economic growth out of 195 countries, with a growth of 4.94 per cent in 2023. Indonesia's growing economy does not escape the threat of fraud. To detect someone committing fraud, signs or symptoms commonly called red flags are needed. The existence of an investigative audit will produce red flags or signals of irregularities. This research aims to find out how investigative audits can detect and reveal corruption by using examples of corruption cases that have occurred as literature studies to be theoretically analysed. This study employs a SLR approach that explores investigative audits from various reference sources. The results of the discussion by dissecting selected literature and reviewing fraud cases that occur, considering the researcher’s findings, it can be said that Cris Kuntadi is the most active researcher in the field of investigative auditing on fraud disclosure. Fraud that occurs can be observed by the presence of red flags in a Perpetrators, Living beyond means or lifestyle is one of the common characteristics of red flags which can be caused by personal financial need to cover this lifestyle